Molecular Simulation of Thermosetting Polymer Hardening: Reactive Events Enabled by Controlled Topology Transfer - Meißner, Robert H.; Konrad, Julian; Boll, Benjamin; Fiedler, Bodo; Zahn, Dirk (Macromolecules, 2020)
We present a nonhybrid quantum mechanical/molecular mechanics (QM/MM) type approach to tackle chemical reactions with substantial molecular reorganization. For this, molecular dynamics simulations with smoothly switched interaction models are used to suggest suitable product states, while a Monte Carlo algorithm is employed to assess the reaction likeliness subject to energetic feasibility. As a demonstrator, we study the cross-linking of bisphenol F diglycidyl ether (BFDGE) and 4,6-diethyl-2-methylbenzene-1,3-diamine (DETDA). The modeling of epoxy curing was supplemented by differential scanning calorimetry (DSC) measurements, which confirm the degrees of cross-linking as a function of curing temperature. Likewise, the heat of formation and the mechanical properties of the resulting thermosetting polymer are found to be in good agreement with previous experiments.
Created from Fastlane, Scopus look-up